I bet you don’t look good on the dance floor: Re-examining the innovation policy dance metaphor in the case of Colombia - Centeno, Juan Pablo; Pinzón-Camargo, Mario A. (NOvation — Critical Studies of Innovation, 2023)
Innovation heuristics offer guidance on how to navigate through the complex dynamics of innovation governance. However, further discussion is needed on the premises of such analytical tools to inquire on their implications on innovation policy and practice. This paper builds on the innovation policy dance metaphor to better grasp the ever-changing interplays (or dance) between innovation practice (I), policy (P) and theory (T). We critically assess the basic underlying assumptions of this metaphor, by examining the extent to which its heuristic pretensions are relevant in the Latin American context. To do so, we explore three illustrative cases in Colombia, shedding light on some crosscutting opportunities and gaps for the dancing metaphor across different innovation I-P-T situations. Some derived lessons suggest that dancing occurs within and/or between different governance levels, where variables such as politics shape the innovation I-P-T interplay and time defines first and second order learning pathways.